2009
DOI: 10.1626/pps.12.50
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Chlorophyll Meter Readings with Gas exchange and Chlorophyll Fluorescence in Flag Leaves of Rice (Oryza sativaL.) Plants

Abstract: fax +81-92-642-2833). Abbreviations : Chl, chlorophyll; F o , initial Chl fl uorescence of a dark-adapted leaf; F m , the maximum Chl fl uorescence of a darkadapted leaf; F v , variable Chl fl uorescence; N, nitrogen; NPT, new plant type; P G , gross photosynthetic rate; PPFD, photosynthetic photon fl ux density; PSII, photosystem II; Rubisco, ribulose-1,5-bisphosphate carboxylase/oxygenase. Abstract : The objective of this study was to establish the correlation of the chlorophyll meter (SPAD) readings with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 17 publications
3
42
0
2
Order By: Relevance
“…On the other hand, a digital chlorophyll meter (Soil and Plant Analyzer Development [SPAD] meter) provides a non-destructive method for estimating leaf chlorophyll content by measuring light absorption of specific spectral bands in living leaves (Watanabe et al 1980;Chubachi et al 1986). The methods for measurement of SPAD values are simple and quick, and close correlations between SPAD values and leaf photosynthesis values have been observed in rice (Huang and Peng 2004;Kato et al 2004;Kumagai et al 2009). Therefore, SPAD measurement may be a more appropriate method than destructive measurement of leaf chlorophyll content for use in genetic analysis of leaf photosynthesis.…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, a digital chlorophyll meter (Soil and Plant Analyzer Development [SPAD] meter) provides a non-destructive method for estimating leaf chlorophyll content by measuring light absorption of specific spectral bands in living leaves (Watanabe et al 1980;Chubachi et al 1986). The methods for measurement of SPAD values are simple and quick, and close correlations between SPAD values and leaf photosynthesis values have been observed in rice (Huang and Peng 2004;Kato et al 2004;Kumagai et al 2009). Therefore, SPAD measurement may be a more appropriate method than destructive measurement of leaf chlorophyll content for use in genetic analysis of leaf photosynthesis.…”
Section: Introductionmentioning
confidence: 86%
“…On the 7th day of waterlogging, the CM readings were significantly lower in the 7-days waterlogged plots compared to non-waterlogged plots in all three years of this experiment ( Figure 4A-C). Previous studies have shown that CM readings were highly correlated with leaf chlorophyll and N content [38][39][40]. In waterlogged treatments, the lower CM readings might have resulted from a decrease in leaf chlorophyll content due to chlorophyll destruction mediated by superoxide radicals formed under waterlogging stress [41][42][43][44].…”
Section: Chlorophyll Meter Readings During Waterloggingmentioning
confidence: 99%
“…In rice, Kumagai et al (2009) correlated PCM readings with some photosynthetic parameters, suggesting that the PCM readings are an indirect indication of the photosynthetic capacity in the flag leaves. In Amaranthus vlitus, there was a linear correlation between PCM readings and some physiological parameters of the leaves, such as photosynthesis, transpiration, and stomatal conductance.…”
Section: Introductionmentioning
confidence: 95%